2014
DOI: 10.14257/ijunesst.2014.7.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Study of Influence Factors of Adaption Intention of Mobile Payment based on TAM Model in China

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
14
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 11 publications
(8 reference statements)
8
14
0
5
Order By: Relevance
“…Also, there is a highly significant positive correlation between perceived ease of use and perceived usefulness (H 3 ), suggesting that customers who recognize that m-payment to be effortless and easy to use also perceive it to be efficient and more useful. Many previous studies have drawn similar outcomes and conclusions (Pousttchi & Wiedemann, 2007;Kim et al, 2010;Schierz et al, 2010;Yongmeng, 2013;Li et al, 2014;Liébana-Cabanillas et al, 2014). Apparently, the current findings confirm the importance of both perceived ease of use and perceived usefulness constructs in predicting individuals' acceptance of m-payment Vol.…”
Section: Discussion Of Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…Also, there is a highly significant positive correlation between perceived ease of use and perceived usefulness (H 3 ), suggesting that customers who recognize that m-payment to be effortless and easy to use also perceive it to be efficient and more useful. Many previous studies have drawn similar outcomes and conclusions (Pousttchi & Wiedemann, 2007;Kim et al, 2010;Schierz et al, 2010;Yongmeng, 2013;Li et al, 2014;Liébana-Cabanillas et al, 2014). Apparently, the current findings confirm the importance of both perceived ease of use and perceived usefulness constructs in predicting individuals' acceptance of m-payment Vol.…”
Section: Discussion Of Resultssupporting
confidence: 86%
“…The current study reinforces the important role subjective norm plays in the adoption process of m-payment technology in Jordan, whereas the present analysis demonstrates that subjective norm is statistically correlated with individuals' behavioral intention to use m-payment. Many studies have reported similar findings (Schierz et al, 2010;Li et al, 2014). Further, in contrary to what has been conceptualized in the current analysis, subjective norm has been found to exert no influence on the perceptions of usefulness (H 5 ).…”
Section: Discussion Of Resultssupporting
confidence: 62%
See 3 more Smart Citations